Co-evolution of tumor and immune cells during progression of multiple myeloma - Ruiyang Liu (Nature Portfolio, 2021)
Clonal evolution in multiple myeloma (MM) needs to be understood in both the tumor and its microenvironment. Here the authors perform single-cell multi-omics profiling of samples from MM patients at different stages, finding transitions in the immune cell composition throughout progression.